Pediatric-type diffuse low grade gliomas: Histomolecular profile and practical approach to their integrated diagnosis according to the WHO CNS5 classification - Suvendu Purkait; Swati Mahajan; Mehar C Sharma; Chitra Sarkar; Vaishali Suri (Wolters Kluwer Medknow Publications, 2022)
Low-grade gliomas are the most common primary central nervous system (CNS) neoplasms in the pediatric age group. The majority of these tumors are circumscribed, while diffuse low-grade gliomas are relatively rare. The pediatric type diffuse low-grade gliomas (pDLGG) have a distinctly different biological behavior, molecular profile, and clinical outcome as compared to their adult counterpart. In the 5th edition of World Health Organization (WHO) CNS classification, pDLGGs are subclassified into four distinct histomolecular entities, namely, (i) diffuse astrocytoma, MYB- or MYBL1-altered, (ii) angiocentric glioma, (iii) polymorphous low-grade neuroepithelial tumor of the young (PLNTY), and (iv) diffuse low-grade glioma, MAPK pathway-altered. Although the molecular profile, to a great extent, aligns with the morphological features, it is not specific. Many of the molecular alterations described in pDLGG have therapeutic implications with the availability of newer targeted therapies. A wide range of testing platforms are available for routine assessment of these molecular alterations in clinical laboratories, though WHO does not recommend any particular method.